miR-140-5p in Small Extracellular Vesicles From Human Papilla Cells Stimulates Hair Growth by Promoting Proliferation of Outer Root Sheath and Hair Matrix Cells - Chen, Yuxin; Huang, Junfei; Liu, Zhen; Chen, Ruosi; Fu, Danlan; Yang, Lunan; Wang, Jin; Du, Lijuan; Wen, Lihong; Miao, Yong; Hu, Zhiqi (Frontiers in Cell and Developmental Biology, 2020)
The application of dermal papilla cells to hair follicle (HF) regeneration has attracted a great deal of attention. However, cultured dermal papilla cells (DPCs) tend to lose their capacity to induce hair growth during passage, restricting their usefulness. Accumulating evidence indicates that DPCs regulate HF growth mainly through their unique paracrine properties, raising the possibility of therapies based on extracellular vesicles (EVs). In this study, we explored the effects of EVs from high- and low-passage human scalp follicle dermal papilla cells (DP-EVs) on activation of hair growth, and investigated the underlying mechanism. DP-EVs were isolated by ultracentrifugation and cultured with human scalp follicles, hair matrix cells (MxCs), and outer root sheath cells (ORSCs), and we found low-passage DP-EVs accelerated HF elongation and cell proliferation activation. High-throughput miRNA sequencing and bioinformatics analysis identified 100 miRNAs that were differentially expressed between low- (P3) and high- (P8) passage DP-EVs. GO and KEGG pathway analysis of 1803 overlapping target genes revealed significant enrichment in the BMP/TGF-β signaling pathways. BMP2 was identified as a hub of the overlapping genes. miR-140-5p, which was highly enriched in low-passage DP-EVs, was identified as a potential regulator of BMP2. Direct repression of BMP2 by miR-140-5p was confirmed by dual-luciferase reporter assay. Moreover, overexpression and inhibition of miR-140-5p in DP-EVs suppressed and increased expression of BMP signaling components, respectively, indicating that this miRNA plays a critical role in hair growth and cell proliferation. DP-EVs transport miR-140-5p from DPCs to epithelial cells, where it downregulates BMP2. Therefore, DPC-derived vesicular miR-140-5p represents a therapeutic target for alopecia.